Knockdown of lncRNA MIR31HG inhibits adipocyte differentiation of human adipose-derived stem cells via histone modification of FABP4 - Yiping Huang (Nature Portfolio, 2017)
Abstract Adipogenesis plays an important role in the regulation of whole-body energy homeostasis and is inextricably related to obesity. Several studies have highlighted the relevance of microRNAs in adipocyte differentiation, but the contributions of long non-coding RNAs (lncRNAs) are still largely uncharacterized. Here, we determined that lncRNA MIR31HG is related to adipocyte lineage commitment. We demonstrated that knockdown of MIR31HG inhibited adipocyte differentiation, whereas overexpression of MIR31HG promoted adipogenesis in vitro and in vivo. Furthermore, inhibition of MIR31HG reduced the enrichment of active histone markers, histone H3 lysine 4 trimethylation (H3K4me3) and acetylation (AcH3), in the promoter of the adipogenic-related gene, fatty acid binding protein 4 (FABP4), leading to suppression of its expression and adipogenesis. These results provide new insights into the molecular mechanisms of MIR31HG in terms of adipogenesis and may have implications for obesity and associated disorders.